Structure, composition and spatial distribution of tree species in a remnant of the semideciduous seasonal Alluvial Forest of the upper Paraná River Floodplain - Campos,João Batista (2000)
The aim of this investigation was to study the structure, distribution patterns, and dynamics of tree species in a remnant of the Semideciduous Seasonal Alluvial Forest in the Upper Paraná River Floodplain, Brazil. Spatial variation of the vegetation was considered mainly in relation to soil and topographic characteristics. The 5,946 m² study area extended along a transect from the bank of the Paraná River across the floodplain, passing through a lake. Phytosociological analysis were performed for 36 plots, each 150 m². Subanalysis were performed for 300 m² zones. Soil characteristics and topographic profile and their relationship to the vegetation were analyzed. Hydrodynamic and sediment processes were the most important factors in vegetation establishment and succession, determining species selection and formation and evolution of the substrate. These processes and their local spatial variability fundamentally affected the dynamics, structure, and patterns of distribution.